Review of Anti-Aging Potential in Aloe vera, Eleuitherine palmifolia, and Hylocereus polyrhizus: A Narrative Literature Review - Fera Anggraeni; Retna Ayu Septiani; Tita Ruhdiana; Nia Yuniarsih (Archives of The Medicine and Case Reports, 2022)
Skin aging is usually characterized by dry, scaly, rough skin conditions accompanied by the appearance of wrinkles and black spots or spots. This literature review aims to discuss the anti-aging potential of Indonesian herbal plants. The aloe vera plant contains various compositions that are useful as skin moisturizers, hair fertilizers, antiseptics, antibiotics, antioxidants, anti-aging, and various other functions. Aloe vera leaves contain vitamins and minerals. One example is vitamin E. Dayak leeks contain an antioxidant IC50 of 45.33 ppm, which can overcome the aging of the skin. Dragon fruit skin contains an antioxidant IC50 of 9.837 mg/mL.